2015
DOI: 10.1162/jocn_a_00776
|View full text |Cite
|
Sign up to set email alerts
|

Prescription Stimulants' Effects on Healthy Inhibitory Control, Working Memory, and Episodic Memory: A Meta-analysis

Abstract: The use of prescription stimulants to enhance healthy cognition has significant social, ethical, and public health implications. The large number of enhancement users across various ages and occupations emphasizes the importance of examining these drugs' efficacy in a nonclinical sample. The present meta-analysis was conducted to estimate the magnitude of the effects of methylphenidate and amphetamine on cognitive functions central to academic and occupational functioning, including inhibitory control, working… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
110
0
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 116 publications
(120 citation statements)
references
References 89 publications
(54 reference statements)
6
110
0
4
Order By: Relevance
“…WM is essential for performing many cognitive tasks ( Wiley & Jarosz, 2012), and individual differences in WM capacity are correlated with individual differences in intelligence (Engle, Tuholski, Laughlin, & Conway, 1999). In part for this reason, the feasibility of enhancing WM has been explored with training (MelbyLervåg & Hulme, 2013), stimulant medications (Ilieva, Hook, & Farah, 2015), and transcranial direct current stimulation (tDCS; Brunoni & Vanderhasselt, 2014). Here, we look more closely into the tDCS and WM enhancement literature.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…WM is essential for performing many cognitive tasks ( Wiley & Jarosz, 2012), and individual differences in WM capacity are correlated with individual differences in intelligence (Engle, Tuholski, Laughlin, & Conway, 1999). In part for this reason, the feasibility of enhancing WM has been explored with training (MelbyLervåg & Hulme, 2013), stimulant medications (Ilieva, Hook, & Farah, 2015), and transcranial direct current stimulation (tDCS; Brunoni & Vanderhasselt, 2014). Here, we look more closely into the tDCS and WM enhancement literature.…”
Section: Introductionmentioning
confidence: 99%
“…Third, by excluding studies for which active and sham stimulation sessions were not counterbalanced, we increased the quality of the analyzed research. Fourth, we selected the most appropriate dependent variable from each study and combined them meta-analytically, following Ilieva et al (2015). As discussed in more detail in the Methods section, under Dependent variables, we used a priori criteria to select dependent variables, rather than separately meta-analyzing accuracy and RT measures and selecting the specific measure of accuracy or RT emphasized by the authors of the original study.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, it is unclear whether ADHD patients are responsive to MPH because of higher DA transporter density (see for review Fusar-Poli et al, 2012); no significant change in NE transporter density have been found (Vanicek et al, 2014). To the best of our knowledge, the monkeys in this study have unimpaired catecholamine systems, but understanding the effects of MPH in healthy subjects is an important step, as stimulants are increasingly being used recreationally as putative cognitive enhancers (McCabe et al, 2005(McCabe et al, , 2014Smith and Farah, 2011;Ilieva et al, 2015). Thus far, evidence for MPH enhancing working memory in the healthy brain is limited, and that its effects on cognition seem modest at most (see for review Ilieva et al, 2015).…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 89%
“…To the best of our knowledge, the monkeys in this study have unimpaired catecholamine systems, but understanding the effects of MPH in healthy subjects is an important step, as stimulants are increasingly being used recreationally as putative cognitive enhancers (McCabe et al, 2005(McCabe et al, , 2014Smith and Farah, 2011;Ilieva et al, 2015). Thus far, evidence for MPH enhancing working memory in the healthy brain is limited, and that its effects on cognition seem modest at most (see for review Ilieva et al, 2015). Our findings that MPH has some beneficial effects on task engagement is consistent with the report from Ilieva and Farah (2013), who suggested that the stimulant-induced enhancement perceived by healthy users has a significant motivational component.…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 99%
See 1 more Smart Citation